Identifikasi Struktur Bawah Permukaan Daerah Potensi Panas Bumi Di Daerah Tulehu Menggunakan Metode Gravitasi - Kurniawan, Indra Reza; Perdhana, Radhitya; Muliadi (Progressive Physics Journal, 2025)
Indonesia has great geothermal potential, Indonesia is located in the path of volcanoes or the ring of fire can also be called the ring of fire. Maluku Province, especially the Ambon and Seram islands, has geothermal energy potential that can be developed as an alternative renewable source. One of the geothermal potentials located in the Maluku islands is WKP Tulehu which has a fairly high temperature reaching 134.09°C–251°C. One method that can be used to identify the subsurface layer of geothermal areas is the gravity method using GGMPlus gravity data. The 2013 Global Gravity Model Plus (GGMPlus) secondary gravity data is a global gravity model data that has ultra–high resolution with grid spacing between data points ~220 m in the north–south direction. The results of the identification of geological structures using gravity methods using regional anomaly values with a range of 80.7–101.3 mgal. The depth of the regional anomaly in the study area is estimated to be 1.862 km deep. There are 7 faults found in the 4 research cross sections. These faults are located in cross section A–A' at a distance of 8.30 km, cross section B–B' at a distance of 1.9 km and 5.1 km, cross section C–C' at a distance of 2.450 km and at a distance of 11.6 km, and cross section D–D' 2.248 km and 4.5 km.